2015
DOI: 10.1097/bte.0000000000000054
|View full text |Cite
|
Sign up to set email alerts
|

Mesh Plates for Scapula Fixation

Abstract: While scapula fractures are often treated nonoperatively, there are a number of displaced fractures in which surgical treatment can be considered. When necessary, open reduction and internal fixation with plates is the accepted method for stabilization. However, there are limited options of commercially available plates for fixation of the scapula. The authors describe 2 cases of scapula fracture and 1 scapula osteotomy that were managed with internal fixation using low-profile mesh plates. The mesh plate is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…The onset of pain occurs, on average, 2 months to 48 months postoperatively. 10,12,16,18,19,33 However, Teusink et al 14 reported a patient with scapular spine fracture 8 years postoperatively. The physiotherapist may report that the patient is progressing slowly with rehabilitation or has deteriorated.…”
Section: Clinical Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…The onset of pain occurs, on average, 2 months to 48 months postoperatively. 10,12,16,18,19,33 However, Teusink et al 14 reported a patient with scapular spine fracture 8 years postoperatively. The physiotherapist may report that the patient is progressing slowly with rehabilitation or has deteriorated.…”
Section: Clinical Evaluationmentioning
confidence: 99%
“…However, the technical challenges of rTSA have resulted in a reported complication rate of 19% to 68%, 3,4,7 with the most common complications including scapular notching, glenoid component loosening/ failure, infection and instability. 2,8 Stress fractures of the shoulder girdle involving the acromion, [9][10][11][12][13][14][15] scapular spine, [16][17][18][19][20][21] clavicle, 22 and coracoid 23 after rTSA are less frequent complications and consequently, they have received limited focus within the upper extremity literature. The more common subset of the aforementioned stress fractures occurs in the acromion and scapular spine in 3.1% to 10% [9][10][11][12][13][14][15]18,19,21 of patients undergoing rTSA and comprises the primary focus of the present review.…”
Section: Introductionmentioning
confidence: 99%
“…Non-displaced fractures detected early can be treated conservatively, but the management of displaced fractures is challenging for the surgeon because of high rates of malunion or nonunion; also, decreased functional acromial fractures after RSA are challenging to treat because of the complex 3-dimensional anatomy, poor bone stock, and variation in fracture patterns, each of which makes stable fixation difficult. 8) When open reduction and internal fixation is the preferred mode for treating displaced lateral acromion fractures, the goal is to apply compression at the fracture site and neutralize the distraction forces of the deltoid. 7) To obtain adequate fixation, several techniques (tension bands, mesh plates, cruciform pilon plates, and locking plates) have been introduced.…”
Section: Discussionmentioning
confidence: 99%
“…7) To obtain adequate fixation, several techniques (tension bands, mesh plates, cruciform pilon plates, and locking plates) have been introduced. [6][7][8][9][10] The previously described tension band-fixation technique resulted in poor functional results for postoperative acromial fractures. 6,7) This fixation method may be insufficient to withstand the forces generated by the deltoid muscle.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, ORIF is more heavily considered with improved clinical outcomes following rigid plate fixation compared with tension band fixation [5•, 50, 51]. Camarada et al and Rouleau et al demonstrated fracture union and good clinical outcomes with the use of a mesh plate and perpendicular 90/90 small fragment locking plate configurations for operative treatment of displaced scapular spine fractures [53,54]. Despite these promising results, this classification system has been shown to have mixed inter-observer reliability [5•, 52, 55].…”
Section: Loss Of Compression: Subscapularis Deficiencymentioning
confidence: 99%